2016
DOI: 10.1007/s11010-016-2735-9
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 protein is downregulated in human hepatocellular carcinoma

Abstract: Annexin A6 (AnxA6) is a lipid-binding protein highly expressed in the liver, regulating cholesterol homeostasis and signaling pathways with a role in liver physiology. Here, we analyzed whether hepatic AnxA6 levels are affected by pathological conditions that are associated with liver dysfunction and liver injury. AnxA6 levels in the fatty liver of mice fed a high-fat diet, in ob/ob and db/db animals and in human fatty liver are comparable to controls. Similarly, AnxA6 levels appear unaffected in murine nonalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Human liver tissues were fixed with formalin and embedded in paraffin. Staining was performed as described elsewhere . Chemerin antibody (BIOZOL Diagnostica) was 1 : 200‐fold diluted.…”
Section: Methodsmentioning
confidence: 99%
“…Human liver tissues were fixed with formalin and embedded in paraffin. Staining was performed as described elsewhere . Chemerin antibody (BIOZOL Diagnostica) was 1 : 200‐fold diluted.…”
Section: Methodsmentioning
confidence: 99%
“…In hepatocytes, AnxA6 is highly abundant, making up approximately 0.25% of total liver protein [ 29 , 30 ]. Our laboratories found hepatic AnxA6 levels unchanged in murine non-alcoholic steatohepatitis and human liver fibrosis, but substantially reduced in hepatocellular carcinoma [ 31 ], which is linked to increased lipogenesis and cholesterol levels [ 32 ]. Other studies reported upregulation of AnxA6 levels in liver biopsies from obese humans and in women with type 2 diabetes [ 33 , 34 ], Niemann-Pick Type C-deficient mice or mice fed a high-fat ketogenic diet [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANXA6 is a member of the annexin family. It is highly expressed in acute myeloid leukemia, pancreatic ductal adenocarcinoma, and hepatocellular carcinoma, and is associated with adverse prognosis [35][36][37][38]. We found that ANXA6 may play the same role in bladder urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 68%